Assessment of the Calorific Value of Charcoal from Gmelina Arborea (Roxb), Tectona Grandis (Linn) and (Bentham) (Global Journal of Science Frontier Research, 2015)
This study was carried out to determine the calorific values of charcoal produced from the wood of Gmelina arborea, Tectona grandis and Pentaclethra macrophylla (Bentham). The purpose of this study is to find out the calorific values of charcoal from these different species at different levels and positions in the tree. The wood species were subjected to three different treatments. The results shows that there were significant differences (p
Keywords: calorific value; charcoal; gmelina arborea; tectona grandis; pentaclethr macrophylla